2013
DOI: 10.7314/apjcp.2013.14.5.3139
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA Methylation of P16, MGMT, hMLH1 and hMSH2 Genes in Combination with the MTHFR C677T Genetic Polymorphism in Gastric Cancer

Abstract: Associations of P16, MGMT, hMLH1 and hMLH2 with gastric cancer and their relation with MTHFR status in gastric patients who were confirmed with pathological diagnosis were assessed. Aberrant DNA methylation of P16, MGMT, hMLH1 and hMLH2 and polymorphisms of MTHFR C677T were assayed. The proportional DNA hypermethylation in P16, MGMT, hMLH1 and hMLH2 in cancer tissues was significantly higher than in remote normal-appearing tissues. DNA hypermethylation of P16 and MGMT was correlated with the T and N stages. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…In addition, novel studies have demonstrated that MTHFR C677T polymorphisms could influence the methylation of MGMT, a gene which was associated with TNM stages of gastric cancer and used as a predictive biomarkers for detecting of gastric cancer. Taken together, these results may further demonstrated the previous results and provided a new insight in prevention of gastric cancer (Chen et al, 2012;Gao et al, 2013;Xiong et al, 2013).…”
Section: Discussionsupporting
confidence: 71%
“…In addition, novel studies have demonstrated that MTHFR C677T polymorphisms could influence the methylation of MGMT, a gene which was associated with TNM stages of gastric cancer and used as a predictive biomarkers for detecting of gastric cancer. Taken together, these results may further demonstrated the previous results and provided a new insight in prevention of gastric cancer (Chen et al, 2012;Gao et al, 2013;Xiong et al, 2013).…”
Section: Discussionsupporting
confidence: 71%
“…The MTHFR is an important enzyme in the one-carbon metabolism pathway that regulates the availability of methyl groups for methylation reactions, and several experimental and epidemiologic studies showed that the MTHFR C677T polymorphism may influence the DNA methylation status [21,23,52]. It has been shown that patients with the MTHFR TT677 genotype have a high risk of DNA hypermethylation in cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous genes have been found to be methylated in GC, including hMLH1, p16, RUNX3, DAPK1, SFRP2 and RNF180. hMLH1 encodes DNA repair proteins and is closely associated with poor prognosis of GC patients; the frequency and specificity were found to be 8.6–80 and 4.1–80%, respectively (1719). P16 inhibits cell cycle progression, and has been found to correlate with poor tumor differentiation, lymph node metastasis and poor survival.…”
Section: Discussionmentioning
confidence: 99%